Identification of Discrete Sites in Yip1A Necessary for Regulation of Endoplasmic Reticulum Structure - Dykstra, Kaitlyn M. (Public Library of Science, 2013)
The endoplasmic reticulum (ER) of specialized cells can undergo dramatic changes in structural organization, including formation of concentric whorls. We previously reported that depletion of Yip1A, an integral membrane protein conserved between yeast and mammals, caused ER whorl formation reminiscent of that seen in specialized cells. Yip1A and its yeast homologue Yip1p cycle between the ER and early Golgi, have been implicated in a number of distinct trafficking steps, and interact with a conserved set of binding partners including Yif1p/Yif1A and the Ypt1/Ypt31 Rab GTPases. Here, we carried out a mutational analysis of Yip1A to obtain insight into how it regulates ER whorl formation. Most of the Yip1A cytoplasmic domain was dispensable, whereas the transmembrane (TM) domain, especially residues within predicted TM helices 3 and 4, were sensitive to mutagenesis. Comprehensive analysis revealed two discrete functionally required determinants. One was E95 and flanking residues L92 and L96 within the cytoplasmic domain; the other was K146 and nearby residue V152 within the TM domain. Notably, the identified determinants correspond closely to two sites previously found to be essential for yeast viability (E76 and K130 in Yip1p corresponding to E95 and K146 in Yip1A, respectively). In contrast, a third site (E89) also essential for yeast viability (E70 in Yip1p) was dispensable for regulation of whorl formation. Earlier work showed that E76 (E95) was dispensable for binding Yif1p or Ypt1p/Ypt31p, whereas E70 (E89) was required. Collectively, these findings suggest that the ability of Yip1A to bind its established binding partners may be uncoupled from its ability to control ER whorl formation. In support, Yif1A knockdown did not cause ER whorl formation. Thus Yip1A may use the sites identified herein to interact with a novel binding partner to regulate ER membrane organization.